Discovery of Genetic Markers of Resistance to β-Lactams in Gramnegative Microorganisms by PCR Diagnosis - E. S. Lisitsina; T. V. Chernenkaya; E. N. Ilyina; I. V. Lazareva; V. A. Ageevets; S. V. Sidorenko (Антибиотики и Химиотерапия, 2020)
Fifteen specimens of the hemoculture and 89 specimens of the broncho-alveolar lavage were used in the study. Monocultures of gramnegative bacteria resistant to cefotaxime, cefepime, imipenem and meropenem were isolated from the specimens. The PCR method with detection of the results in the real time regimen (PCR test-system Litekh) provided detection of the beta-lactamase genes: bla/CTX- M-like (72/104, 69.2%), blaNDM (6/104, 5.8%), blaVIM (49/104, 47,1%) and blaOXA48_like (59/104, 56.7%). There was identified correlation between the phenotype of resistance of Acinetobacter spp., Pseudomonas aeruginosa, Klebsiella pneumoniae and Escherichia coli to cefotaxime and carbopenems and detection of the blaCTX_M_like and blaNDM genes. At the same time, up to 70% of the K.pneumoniae isolates from the biological specimes positive with respect to the presence of the carbapenase blaVIM and blaOXA48-like genes demonstrated their phenotypic susceptibility to carbopenems. The results of the study confirmed the prognostic value of the genetic diagnosis for improvement of the routine bacteriological investigations.